Who are those people we call farmers? Rural Kenyan aspirations and realities. Issue 4 (19th May 2018) - Verkaart, Simone; Mausch, Kai; Harris, Dave
ABSTRACT: Rural Kenyan households have different aspirations and income portfolio strategies, including agricultural intensification and income diversification. This article reports on a study that interviewed 624 households to explore rural aspirations and derive lessons for agricultural technology development and transfer. Though few households specialised in farming, many households self-identified as farmers and aspired to increase their agricultural income. Despite the prevalence of agricultural aspirations, few aspired for their children to have a future in farming. Combining aspirations with potential to invest, the article provides suggestions for targeting agricultural interventions. We need to start listening better to those people we call "farmers" to develop and offer innovations that meet their realities.